Knowledge of politician stock trading reduces congressional legitimacy and compliance with the law - Raihan Alam; Tage S. Rai (Proceedings of the National Academy of Sciences, 2025)
Institutional legitimacy is essential for democracies, yet public trust and confidence in the United States Congress are at an all-time low. A significant predictor of attitudes toward Congress is perceptions of corruption, with perceptions of corruption in government linked to less legitimacy. This study tests whether knowledge of Congressional stock trading affects legitimacy and compliance with Congressional authority. In a preregistered experiment with US citizens ( n = 506), participants who read a report detailing how Congressmembers made higher-than-expected profits from stock trading in 2024 reported increased perceptions of corruption and decreased legitimacy in Congress. They also viewed laws passed by Congress as less fair and were less willing to comply with such laws. Perceptions of Congressional legitimacy mediated the effect of stock trading knowledge on willingness to comply with congressional laws and perceptions of congressional laws as fair. A preregistered follow-up experiment ( n = 664) shows that these effects are not driven by how much Congressmembers profit but by how trading negatively affects broader perceptions of legitimacy. These findings highlight the detrimental effects of Congressional stock trading on perceptions of legitimacy and respect for the law.